Penerapan Media Pembelajaran Audio-Visual dalam Meningkatkan Hasil Belajar Senam Guinness World Records (Gwr) pada Mahasiswa Penjas universitas Dehasen Bengkulu - Hendra Irawan; Martiani Martiani; Supriyanto Supriyanto (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2020)
The research aimed to determine the learning outcomes of Guiness World Records (GWR) gymnastics using audio-visual learning media scientifically. This research is a classroom action research (PTK) with 44 research subjects from the FKIP Phisical Education Study Program Dehasen University of Bengkulu. This class action research procedure is: (1) planning (2) implementing class actions (actions), (3) observation and reflection in each cycle. In the first cycle, student learning outcomes that reached a minimum score (60) were 25 people with a mean value of 63.43 and a success rate of 56.8% of the total number of samples. The study continued in cycle II, with student learning outcomes of 38 people exceeding the minimum grade with a success rate of 86.4% of the total sample. With these results it can be concluded that the learning carried out gives positive results, namely improving student learning outcomes and the research is declared successful because it has reached the classical completeness value of 85%. Kata Kunci : Audio-Visual Learning Media, Gymnastics Learning Outcomes